Accuracy of touch method for assessing temperature in newborn - Anto, Ancy Anto; Mathew, Shiny; Shekharappa, Chandrakala Bada (Indian Journal of Child Health, 2018)
Introduction: Early recognition of hypothermia by the mother or a health worker is crucial to institute corrective actions to improve the survival of newborn babies. Hand-touch technique is a simple, practical, and inexpensive method that has been promoted for assessing neonatal hypothermia in resource-poor countries. Objective: The objective of this study is to compare the accuracy of touch method as assessed by mothers with the axillary method (standard technique) and to find the association of maternal variables with the accuracy of touch method. Materials and Methods: In this diagnostic study, postnatal babies with birth weight >2 kg and gestation >35 weeks were included within 24 h of birth after the parental consent. Those babies who were shifted to neonatal intensive care unit were excluded from the study. Investigator demonstrated the touch method of assessing temperature to the mother, and the temperature assessed by the mothers was then compared with the standardized temperature measurement technique in the axilla. Babies were classified into two groups, i.e., hypothermia or no hypothermia (normothermia). Results: A total of 82 mother-baby dyads were studied. Of 22 (26.83%) babies, who were hypothermic by axillary temperature, mothers could correctly categorize only 11 (50%) babies as hypothermic by touch method. Of 60 (73.17%) babies who had normal temperature as assessed by axillary method, 40 (66.67%) babies were correctly categorized as normothermic by touch technique. Sensitivity, specificity, positive predictive value, and negative predictive value of touch method by the mother and the investigator was 50%, 66%, 35.48%, and 78.43% and 78.33%, 81.82%, 92.16%, and 58.06%, respectively. Conclusion: The sensitivity of the touch method as assessed by the mother to detect hypothermia is poor. However, adequate and frequent training and experience of the mother can improve the sensitivity. The study could be recommended to perform with larger sample size.